Gender and collusion - Justus Haucap; Christina Heldman; Holger A. Rau (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2022)
Many cartels are formed by individual managers of different firms, but not by firms as collectives. However, most of the literature in industrial economics neglects individuals' incentives to form cartels. Although oligopoly experiments reveal important insights on individuals acting as firms, they largely ignore individual heterogeneity, such as gender differences. We experimentally analyze gender differences in prisoner's dilemmas, where collusive behavior harms a passive third party. In a control treatment, no externality exists. To study the influence of social distance, we compare subjects' collusive behavior in a within-subjects setting. In the first game, subjects have no information on other players, whereas they are informed about personal characteristics in the second game. Results show that guilt-averse women are significantly less inclined to collude than men when collusion harms a third party. No gender difference can be found in the absence of a negative externality. Interestingly, we find that women are not sensitive to the decision context, i.e., even when social distance is small they hardly behave collusively when collusion harms a third party.
Keywords: C92; D01; D43; J16; K21; L13; L41; 330; Collusion; Cartels; Competition Policy; Antitrust; Gender Differences